2010
DOI: 10.3346/jkms.2010.25.s.s41
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Reproductive Function Abnormalities and Bladder Cancer in Korea

Abstract: The purpose of this study was to review occupational reproductive abnormalities and occupational bladder cancer in Korea and to discuss their toxicological implications. Reproductive dysfunction as a result of 2-bromopropane poisoning was first reported in Korean workers. In 1995, 23 of the 33 workers (25 female and 8 male workers) who were exposed to 2-bromopropane during the assembly of tactile switch parts developed reproductive and/or hematopoietic disorders. A total of 17 (68%) workers were diagnosed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Because of the detrimental effects on the ozone layer caused by chlorofluorocarbons and the ban on their use, 1-BP and 2-BP were previously used in Asia as substitute propellants and cleaning solvents [146]. In the mid 1990s, an occupational health manager reported that a cluster of women performing small-sized tactile switch assembly in an electronics factory in South Korea were experiencing amenorrhea [147,148]. 2-BP had been introduced into the electronics plant in early 1994 as a substitute solvent for chlorofluorocarbons.…”
Section: Occupational Chemicalsmentioning
confidence: 99%
“…Because of the detrimental effects on the ozone layer caused by chlorofluorocarbons and the ban on their use, 1-BP and 2-BP were previously used in Asia as substitute propellants and cleaning solvents [146]. In the mid 1990s, an occupational health manager reported that a cluster of women performing small-sized tactile switch assembly in an electronics factory in South Korea were experiencing amenorrhea [147,148]. 2-BP had been introduced into the electronics plant in early 1994 as a substitute solvent for chlorofluorocarbons.…”
Section: Occupational Chemicalsmentioning
confidence: 99%
“…1 At diagnosis approximately 70% of cancers are nonmuscle invasive tumors and the remaining 30% are muscle invasive. 2 About 10% of the patients diagnosed with these muscle invasive tumors have metastatic disease with a poor prognosis.…”
mentioning
confidence: 99%
“…Brown et al ( 13 ) reported an increased risk of bladder cancer among individuals exposed to benzidine. Furthermore, Park et al ( 14 ) reported a number of cases of benzidine-induced occupational bladder cancer in Korea. However, although there are numerous reports on the risk of bladder cancer associated with benzidine exposure, there is paucity of data regarding the effect of benzidine on BCSCs, and the mechanism underlying the promoting role of benzidine in BCSCs remains elusive.…”
Section: Introductionmentioning
confidence: 99%